(untitled) (International Seven Journal of Multidisciplinary, 2023)
Considering that research into the survival and growth of forest species via direct sowing in the improved cerrado of Roraima is still scarce, this research adds information to this technique with six forest species in relation to emergence, survival and increase in plant height and diameter over 18 months. In view of the above, the aim was to indicate procedures for direct sowing of forest tree species (pau-rainha, maçaranduba, freijó, jatobá, itaúba and African mahogany) in a cerrado area of Roraima, using shrub legumes, as a way of dispensing with the formation and management of seedlings in nurseries and enabling the establishment of forest plantations at reduced costs. Thus, in the experimental area, each species, maçaranduba, freijó, jatobá, itaúba, pau-rainha and African mahogany in July 2021 were sown 50 cm apart in the row and two seeds were distributed at a depth of up to 1 cm depending on the size of the seed. The experiment occupied a total area of 4,500 m2 and a useful area with sown seeds of 3,456 m2, totaling 648 seeds per species. The percentage of emergence was assessed at 120 days after sowing, and seedling survival at 6, 12 and 18 months. In addition, increments in height and diameter were assessed from 6 to 12 months and from 12 to 18 months. Of the six forest species studied, 2% (pau-rainha), 6% (African mahogany) and 53% (jatobá) showed seedling emergence, with the latter, jatobá, surviving >80% after 18 months. In the same period, African mahogany and Pau-rainha had a survival rate of 50%. Direct sowing in Roraima’s improved cerrado for Jatobá is recommended. The procedure used to promote an increase in the stem diameter (ΔDC) of jatobá plants from direct sowing via seeds from six to 18 months is the application of 3.0 t ha-1 of limestone and 1.8 t ha-1 of agricultural gypsum in the cerrado of Roraima, and is a species suitable for establishing forest plantations at a cost of 1.55 reais per seedling.